Compatibility of Plant Growth-promoting Rhizobacterial Strains to the Integrated Specific Nutrient Mixture Formulated for Lateritic Soils of Goa - Maneesha, S. R.; Ramesh, R.; Mahajan, G. R.; Verenkar, Deepika Shet; Gaonkar, Tulsi; Kulkarni, Rahul; Chakurkar, E. B. (International Journal of Economic Plants, 2025)
The experiment was conducted from January to August, 2017 at ICAR-Central Coastal Agricultural Research Institute, Old Goa, Goa to study the compatibility of the plant growth-promoting rhizobacterial strain to the integrated specific nutrient mixture (ISN mix) prepared to alleviate the multinutrient deficiency of the laterite soils of Goa. The mixture was composed of organic manures and inorganic secondary and micronutrients. The ISN mix had a neutral to slightly alkaline pH of 7.78 with a particle density of 0.48 mg m-3. The mixture contained 0.806% N, 0.163% P, 1.09% K, 0.226% S, 1111 mg kg-1 Ca, 139.3 mg kg-1 Mg, 5394 mg kg-1 Fe, 66.68 mg kg-1 Mn, 6480 mg kg-1 Zn, 57.36 mg kg-1 Cu and 477 mg kg-1 B. This mixture was mixed with the locally isolated and well-characterized plant growth-promoting rhizobacteria Bacillus methylotrophicus strains STC-4 and Rch6-2b. The compatibility of these strains with the native microbial population already existing in the ISN mixture was tested, and positive results were observed. Further, its compatibility was tested with the ISN mixture containing organic and inorganic components in 2%, 5%, and 10% talc formulations. Both strains were compatible with the ISN mix with a 9.01x109 log CFU g-1 population for up to 6 months in all the concentrations. For the fortification of the ISN mix, the salt-tolerant strain, STC-4 was selected at a 5% concentration. The effect of ISN mix on plant growth, yield and quality need to be studied further.